2021
DOI: 10.1016/j.apcata.2021.118264
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid CoMoS - polyaniline nanowires catalysts for hydrodesulfurisation applications

Abstract: Liquid and gas phase sulfidation conditions of MoOx/PANI hybrids result in different MoSx phases • Active CoMoS phase content in the final catalysts deposited through a surface reaction using cobalt acetylacetonate depends on the nature of starting Mo based PANI materials.The formation of mixed sites is favored when Mo and Co sulfidations are simultaneous.• CoMoS/PANI showed much better catalytic activities than the CoMoS counterpart prepared without PANI• HDS of 3-methylthiophene is correlated to the Co/Moedg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“… a MoS 2 crystallite size (S), b average stacking (St), c average length (L), normalD=4ptnormalMnormalo4ptnormalenormaldnormalgnormalenormals+normalcnormalonormalrnormalnnormalenormalrnormalMnormalo4ptnormaltnormalonormaltnormalanormall=4pti6ni-6i3nnormali2-3ni+1 ${{\rm D}={\rm \ }{{{\rm M}{\rm o}{\rm \ }{\rm e}{\rm d}{\rm g}{\rm e}{\rm s}+{\rm c}{\rm o}{\rm r}{\rm n}{\rm e}{\rm r}}\over{{\rm M}{\rm o}{\rm \ }{\rm t}{\rm o}{\rm t}{\rm a}{\rm l}}}={\rm \ }{{\sum _{{\rm i}}6{{\rm n}}_{{\rm i}}-6}\over{\sum _{{\rm i}}3{{\rm n}}_{{\rm i}}^{2}-3{{\rm n}}_{{\rm i}}+1}}}$ with n i : number of Mo atoms along one side of a MoS 2 slab determined from its length and i being the total number of slabs measured by TEM [36] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a MoS 2 crystallite size (S), b average stacking (St), c average length (L), normalD=4ptnormalMnormalo4ptnormalenormaldnormalgnormalenormals+normalcnormalonormalrnormalnnormalenormalrnormalMnormalo4ptnormaltnormalonormaltnormalanormall=4pti6ni-6i3nnormali2-3ni+1 ${{\rm D}={\rm \ }{{{\rm M}{\rm o}{\rm \ }{\rm e}{\rm d}{\rm g}{\rm e}{\rm s}+{\rm c}{\rm o}{\rm r}{\rm n}{\rm e}{\rm r}}\over{{\rm M}{\rm o}{\rm \ }{\rm t}{\rm o}{\rm t}{\rm a}{\rm l}}}={\rm \ }{{\sum _{{\rm i}}6{{\rm n}}_{{\rm i}}-6}\over{\sum _{{\rm i}}3{{\rm n}}_{{\rm i}}^{2}-3{{\rm n}}_{{\rm i}}+1}}}$ with n i : number of Mo atoms along one side of a MoS 2 slab determined from its length and i being the total number of slabs measured by TEM [36] …”
Section: Resultsmentioning
confidence: 99%
“…i À 3ni þ1 with n i : number of Mo atoms along one side of a MoS 2 slab determined from its length and i being the total number of slabs measured by TEM. [36] ChemCatChem analyzed when comparing data for NiMoS-7 (Figure 6a, Figure 7a) and NiMoS-7-P123 (Figure 6c, Figure 7c).…”
Section: Chemcatchemmentioning
confidence: 99%
“…Polyaniline (PANI)-supported MoS 2 was synthesized following the reported literature with slight modifications [23]. The starting material, molybdenum oxide supported on PANI (MoO x /PANI), was synthesized following our recent report [24]. In a typical hydrothermal synthesis, 2 g of as-prepared MoO x /PANI (S BET = 8 m 2 /g, 38.7 wt% Mo) was dispersed in 100 mL of deionized water via ultrasonication for 1 h at 30 • C and 1.5 g thiourea (corresponding to a S/Mo molar ratio of 2.1) was added subsequently.…”
Section: Synthesis Of Mos 2 /Panimentioning
confidence: 99%
“…De Castro et al [17, 18] explored Co‐Mo‐S materials in hydrodeoxygenation and hydrotreating, opening novel pathways for catalyst design. Ghosh et al [19, 20] identified Co‐Mo‐S's promising catalytic efficiency and circular economy potential in hydrodesulfurization reactions, laying the foundation for catalyst advancement. Lastly, Zheng et al [21] utilized density functional theory to analyze different sulfur compounds' hydrodesulfurization mechanism on the active phase of Co‐Mo‐S, with the edge highlighted as the primary active site.…”
Section: Introductionmentioning
confidence: 99%